THE INFLUENCE OF RURAL DEVELOPMENT PROGRAMMES ОN AGRICULTURAL LAND USE IN UKRAINE - Roman KURYLTSIV; Nadiya KRYSHENYK (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The article deals with the implementation of the State Target Program on Ukrainian Village Development of Ukraine. The aim of the paper was to present the influence Ukrainian Village Development Programme 2007 – 2015 on agricultural land use taking into account its objectives. This topic is current in the context of the Village Development Programme 2007 – 2015 evaluation and search for effective tools for supporting agricultural land use. The results of research conducted in 2017 based on the data of Ministry of Agrarian Policy and Food of Ukraine and Accounting Chamber of Ukraine are presented. During the period of the State Program, about a half part of the projected amount of funds was allocated from the budget on agricultural market development. Consequently, ineffective state management and limited budget funding did not contribute to the efficient use of agricultural land by rural areas and the achievement of the expected results of the Village Development Program.